Reinforcing Neo-Sufism in the Malay-Indonesian World: Shaṭṭārīyah Order in West Sumatra - Fathurahman, Oman (Studia Islamika, 2003)
The article looks at the dynamics and developments in Neo-Sufist teachings from the 19th century until the mid-20th century, using the Shattariyyah order in West Sumatra as a case study. Along with looking at the spread of the Shattariyyah order in West Sumatra by way of Shaikh Burhanuddin Ulakan, a key figure in the order, this discussion will also focus on how Shattariyyah spread in this region, what changes took place in terms of the teachings of neo-Sufism, especially during the later period (19th and 20th centuries), and the nature of the Shattariyyah teacher- student silsilah (genealogy) in West Sumatra.DOI: 10.15408/sdi.v10i3.623